2019
DOI: 10.1136/bmjopen-2018-026315
|View full text |Cite
|
Sign up to set email alerts
|

Haemorheological and haemostatic alterations in coeliac disease and inflammatory bowel disease in comparison with non-coeliac, non-IBD subjects (HERMES): a case–control study protocol

Abstract: IntroductionHaemorheological and haemostatic changes predispose to the development of arterial and venous thrombotic events; however, limited information is available on the status of these changes in coeliac disease (CeD) and inflammatory bowel disease (IBD). In this study, we aim to describe the haemorheological and haemostatic profiles of CeD and IBD patients in a Hungarian cohort of patients to investigate whether any alterations contribute to elevated thrombotic risk.Methods and analysisThis is a case–con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…6917) and registered in the ISRCTN Registry under registration number ISRCTN49677481. Full technical details of the protocol are published elsewhere ( 28 ). This report follows the STROBE Statement ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…6917) and registered in the ISRCTN Registry under registration number ISRCTN49677481. Full technical details of the protocol are published elsewhere ( 28 ). This report follows the STROBE Statement ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Control subjects were individuals in whom CeD was excluded by the treating gastroenterologist specialist ( 30 , 31 ). Exclusion criteria from the study are detailed in the prestudy protocol ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, multiple other reports appeared to suggest the connection [ 10 , 11 , 12 ], although various observational studies and meta-analyses have found conflicting results [ 13 , 14 , 15 , 16 , 17 ]. A number of well-designed prospective studies are ongoing in an attempt to understand this association and provide definitive answers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%